PENGARUH JUMLAH INDUSTRI, TENAGA KERJA, DAN PENGELUARAN PEMERINTAH TERHADAP PERTUMBUHAN EKONOMI DI KAWASAN GERBANGKERTASUSILA TAHUN 2014-2018 - Anggie Triteleiea Laxa; Aris Soliestyo (Jurnal Ilmu Ekonomi, 2020)
GERBANGKERTASUSILA in East Java Province is the highest contributor to GRDP in East Java Province. The purpose of the research itself is to determine the influence of the number of industries, labor, and government spending with economic growth in the GERBANGKERTASUSILA region in 2014-2018. In this study, the Gross Regional Domestic Product (GRDP) data on the number of industries, labor in the industrial sector, and government expenditure in the industrial sector over a period of five years is 2014-2018. The method in this study uses Panel Data which is a combination of time series data (2014-2018) and cross data (seven regencies / cities) in East Java Province as well as the Random Effect approach model. The data analysis of this study used multiple linear regression with the source of the data obtained from BPS (Statistics Indonesia) which then processed the data using Eviews-9. The results of this study indicate that each variable of the number of industries, labor, and government spending has a significant and positive influence on economic growth in the GERBANGKERTASUSILA region in 2014-2018.